Survey on Demographics in Social Media - Kotaiah Swamy Kakulla, Dr.K.F.Bharati (International Journal of Advanced Science and Technology, 2020)
Demographics data is most widely used in many applications for the research point of view. For the use of different types of problems the demographics data is used. Nowadays in many applications data is gathering in various types to solve some of the issues with demo graphics data. Demographic data is used in many fields such as public health, and there is a lot of variations that can exist based on sex, racial and socioeconomic groups. To overcome the issues in studies various machine learning (ML) and deep learning (DL) algorithms are proposed to analyze the demographics data in various domains. In this paper, the survey is continues on various demographics data used in various applications and these measures the improved accuracy with ML and DL algorithms.